Pelatihan dan Penerapan Diabetes Self Management Education pada Pasien dan Keluarga untuk Meningkatkan Efikasi Diri Penderita Diabetes Mellitus: Training and Implementation of Diabetes Self Management Education for Patients and Families to Increase Self-Efficacy of Patients with Diabetes Mellitus - Zulkarnaini, Zulkarnaini; Hayani, Nora; Idwar, Idwar; Azwarni, Azwarni; Yusrawati, Yusrawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Diabetes Mellitus is one of the chronic diseases and every year the number of sufferers is increasing in various parts of the world. This disease is a metabolic disorder in which the body is impaired in using glucose, protein, and fat due to insulin deficiency or insulin resistance. There are 422,000,000 people worldwide suffering from diabetes mellitus, mostly in low- and middle-income countries and about 1,600,000 deaths are associated with diabetes mellitus every year. This service aims to increase the knowledge, insight, and independence of patients in implementing Diabetes Self Management Education with the family to increase the self-efficacy of patients with diabetes mellitus. The method of this community service is training by providing Diabetes Self Management Education material to be applied in the patient's daily life. Participants are patients with diabetes mellitus and the closest family as patient companions, which was carried out at the Langsa Kota Health Center on May 29 - June 12, 2024. The results of this service were obtained before the intervention the majority of participants had moderate knowledge (78%) and after the intervention the majority had good knowledge (89.1%), there was also an increase in self-efficacy from before the intervention the majority was moderate (64%) after the intervention, the level of self-efficacy of the participants increased with a high majority (78.3%). It is recommended that health facilities apply diabetes self-management education to diabetics because if diabetics understand this self-management, they can manage their health wisely and increase self-efficacy.